A sequence { x n } is defined as follows: x 1 = 1 , x n + 1 = x n 2 + 2 x n ( n = 1 , 2 , 3 , ⋯ ) . Find x 7 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I'll add a small but very useful observation that hasn't yet been mentioned. We can complete the square in the given iteration formula to bring it in this form: x n + 1 = x n 2 + 2 x n = ( x n 2 + 2 x n + 1 ) − 1 = ( x n + 1 ) 2 − 1 ⇔ x n + 1 = ( x n + 1 ) 2 − 1
Now we can very easily plug in values for x 1 , x 2 , . . . , x 6 . Here are the steps in detail:
x
2
=
(
1
+
1
)
2
−
1
=
2
2
−
1
Do NOT make the mistake of writing this as
x
2
=
5
. We are working with powers of
2
here.
x
3
=
(
2
2
−
1
+
1
)
2
−
1
=
2
4
−
1
x
4
=
(
2
4
−
1
+
1
)
2
−
1
=
2
8
−
1
x
5
=
(
2
8
−
1
+
1
)
2
−
1
=
2
1
6
−
1
x
6
=
(
2
1
6
−
1
+
1
)
2
−
1
=
2
3
2
−
1
x
7
=
(
2
3
2
−
1
+
1
)
2
−
1
=
2
6
4
−
1
⇔
x
7
=
2
6
4
−
1
Problem Loading...
Note Loading...
Set Loading...
Computing values for n = 2 , 3 , 4 we see
x 2 = 2 2 − 1
x 3 = 2 4 − 1
x 4 = 2 8 − 1
So the sequence can be shown by induction to be x n = 2 2 n − 1 − 1 . So plugging in n = 7 we find x 7 = 2 6 4 − 1 .